(untitled) (Al-Aasar, 2025)
The study examined the moderating effect of personality traits between the relationship between religious orientation and intellectual humility. Participants in this study were involved 357 college teachers (male=178, female=179) of nine districts of Pakistan using convenience sampling. Data were collected through Comprehensive Intellectual Humility Scale and Religious Orientation Scale and Big Five Inventory. Correlational analysis showed that religious orientation; intrinsic and extrinsic, intellectual humility and personality traits have a positive significant relationship. The findings of hierarchical regression revealed that intellectual humility was a significant predictor of religious orientation, as well as personality traits moderated the relationship between intrinsic and extrinsic religious orientation and intellectual humility. Three of the personality traits; extraversion, openness and agreeableness and have considerably moderated the relationship between intrinsic and extrinsic religious orientation and intellectual humility whereas, neuroticism negatively moderates the relationship between variables. This study potentially can uplift more harmonious and empathic interactions with diverse religious beliefs and orientations in university environments.